Sugar and spice : an L.A. candy novel - Conrad, Lauren (New York : Harper, 2010)
Reality television star Jane Roberts never imagined how celebrity would change her life, and now she must decide if the fame and glamour are worth the drama and deception.
014-017.
Keywords: Reality television programs -- Juvenile fiction; Celebrities -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Conduct of life -- Juvenile fiction; Los Angeles (Calif.) -- Juvenile fiction; Fiction; Juvenile works